The Effect of Cooperative Learning Model on the Improvement of Basketball Skills among University Students - Lalu Moh Yudha Isnaini; Gosy Endra Vigriawan; Suharti; Pinton Setya Mustafa; Lalu Moh Yudha Isnaini; Gosy Endra Vigriawan; Suharti; Pinton Setya Mustafa (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
The objective of this research was to analyze the impact of the cooperative learning model on the enhancement of basketball skills in university students. A pre-experimental one-group pre-test–post-test design was used in this study with 38 undergraduate students attending a basketball class. The intervention was carried out over eight weeks (16 sessions) using structured cooperative learning strategies such as positive interdependence, individual accountability and peer interaction. Basketball skills were assessed using standardized tests measuring dribbling, passing, and shooting performance. Data were analyzed using descriptive statistics and paired-samples t-tests, with effect sizes calculated using Cohen’s d where α was set to 0.05. All skill components demonstrated statistically significant increases (p < 0.001). Improvements in dribbling performance were evidenced by decreased completion times, while passing and shooting accuracy significantly increased. The overall skills score improved by 18.34%, again with large effect sizes (d = 0.95–1.20). The cooperative learning model was effective in improving basketball skills of university students. These results provide grounds for implementing student-centered teaching methods in higher education physical education contexts.